2016 IEEE International Conference on Cloud Computing Technology and Science (CloudCom) 2016
DOI: 10.1109/cloudcom.2016.0107
|View full text |Cite
|
Sign up to set email alerts
|

EDISON Data Science Framework: A Foundation for Building Data Science Profession for Research and Industry

Abstract: Data Science is an emerging field of science, which requires a multidisciplinary approach and should be built with a strong link to emerging Big Data and data driven technologies, and consequently needs rethinking and redesign of both traditional educational models and existing courses. The education and training of Data Scientists currently lacks a commonly accepted, harmonized instructional model that reflects by design the whole lifecycle of data handling in modern, data driven research and the digital econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 4 publications
0
17
0
2
Order By: Relevance
“…The lack of preparedness for Malaysian firms can be attributed to personnel expertise. Hence, whilst the information technology is present, there is yet to be a sufficient pool of data qualified and experienced personnel, similar to what other research has found [153][154][155]. Malaysia also, may be facing such a situation, as also found by other research [156].…”
Section: Capabilities and Process-eco-innovationmentioning
confidence: 69%
“…The lack of preparedness for Malaysian firms can be attributed to personnel expertise. Hence, whilst the information technology is present, there is yet to be a sufficient pool of data qualified and experienced personnel, similar to what other research has found [153][154][155]. Malaysia also, may be facing such a situation, as also found by other research [156].…”
Section: Capabilities and Process-eco-innovationmentioning
confidence: 69%
“…For example, as noted above, LEADING adapts National Science Foundation's (NSF) Big Data Innovation Regional Hub model, which features both partner hubs and membership nodes, thus encouraging sustained growth. Further, LEADING's bootcamp curriculum aligns with that of EDISON, which is similarly helpful for developing and expanding networks and thus for promoting sustainability (Demchenko et al, 2017(Demchenko et al, , 2016Manieri et al, 2015;Wiktorski et al, 2017Wiktorski et al, , 2016. Finally, LEADING features yearly (2021 and 2022) OCLC-sponsored data science challenges, in which Fellows and other students and information professionals will generate and share via LEADING's GitHub page curriculum materials based on OCLC data, and a summative PI-and Fellows-led outreach workshop, the curriculum work of which will also be shared via GitHub.…”
Section: Lis Education and Data Science-integrated Network Group (Leading)mentioning
confidence: 99%
“…With regard to ICT-related competences, the European "e-Competence Framework" provides 40 competences, including skills and knowledge requirements, which can be used across Europe [12]. Similarly, the EDISON project is working on the development of a "Data Science Competences Framework" that includes: competence groups, big data and analytics tools and programming languages [13].…”
Section: Related Workmentioning
confidence: 99%